2014
DOI: 10.1371/journal.pone.0096842
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study between Solenopsis invicta and Solenopsis richteri on Tolerance to Heat and Desiccation Stresses

Abstract: Solenopsis invicta and Solenopsis richteri are two very closely related invasive ant species; however, S. invicta is a much more successful invader. Physiological tolerance to abiotic stress has been hypothesized to be important to the success of an invasive species. In this study, we tested the hypothesis that S. invicta is more tolerant to heat and desiccation stress than S. richteri. The data strongly support our hypothesis. S. invicta was found to be significantly less vulnerable than S. richteri to both h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…richteri ). The higher number of replicates in the study by Chen et al [ 45 ] could have contributed to the detection of significant differences in their study. The body water content values recorded for all four Solenopsis spp.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…richteri ). The higher number of replicates in the study by Chen et al [ 45 ] could have contributed to the detection of significant differences in their study. The body water content values recorded for all four Solenopsis spp.…”
Section: Discussionmentioning
confidence: 96%
“…invicta and S . richteri have been reported to be significantly different [ 45 ]. However, our data show no body water content difference for combined sizes of workers of both the tropical/subtropical species ( S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. invicta first became invasive in the USA, where it is currently outcompeting the earlier invaders S. geminata and S. richteri, and subsequently invaded in many other parts of the world. In the USA, S. invicta displays better acclimatization than S. geminata to extremes in temperature, relative humidity and light levels (Wuellner and Saunders, 2003), and it also shows more tolerance than S. richteri to heat and desiccation (Chen et al, 2014). A series of studies also revealed that S. invicta better responds to habitat disturbance than S. geminata (Plowes et al, 2007;LeBrun et al, 2012;Axen et al, 2014) and displays higher potential of dispersal than S. geminata, being able to engage in mating flights earlier in the season (Tschinkel, 2006) and to produce larger colonies on average (Trible et al, 2018).…”
Section: Fire Antsmentioning
confidence: 99%
“…The volcanic ash with the sharp ash particles will lead to reduced survival, growth, and dehydration tolerance due to increased water loss through the damaged cuticle (Edwards and Schwartz, 1981). Indeed, the cuticle beneath the lipid layer protects from desiccation in ants Solenopsis invicta and S. richteri (Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%